Police officers’ job satisfaction: combining public service motivation and person-environment fit - White, David R. (Journal of crime and justice, 2022)
This study examines front-line police officers’ job satisfaction in mid-sized municipal departments in the Midwestern United States. We use a 2019 cross-sectional survey of seven police departments (N = 234) to examine the relationships between officers’ job satisfaction and their public service motivations (PSM), perceptions of person-environment fit with three referent groups – top managers, supervisors, and coworkers – and their perceptions of self-legitimacy. The results suggest that organizational fit with top managers, PSM, and officers’ self-legitimacy are all positively related to job satisfaction, explaining nearly half of the variance in the sample. Using multiple regression models, we explore the potential mediating effects of fit on PSM but find little support for this proposition. Among individual-level control variables that were assessed, only tenure was significantly (negatively) related to job satisfaction.